C–H activation and nucleophilic substitution in a photochemically generated high valent iron complex - Lim, Jia Hui (2018)
The photochemical oxidation of a (TAML)FeIII complex 1 using visible light generated Ru(bpy)33+ produces valence tautomers (TAML)FeIV (1+) and (TAML˙+)FeIII (1-TAML˙+), depending on the exogenous anions. The presence of labile Cl− or Br− results in a ligand-based oxidation and stabilisation of a radical-cationic (TAML˙+)FeIII complex, which subsequently leads to unprecedented C–H activation followed by nucleophilic substitution on the TAML aryl ring. In contrast, exogenous cyanide culminates in metal-based oxidation, yielding the first example of a crystallographically characterised S = 1 [(TAML)FeIV(CN)2]2− species. This is a rare report of an anion-dependent valence tautomerisation in photochemically accessed high valent (TAML)Fe systems with potential applications in the oxidation of pollutants, hydrocarbons, and water. Furthermore, the nucleophilic aromatic halogenation reaction mediated by (TAML˙+)FeIII represents a novel domain for high-valent metal reactivity and highlights the possible intramolecular ligand or substrate modification pathways under highly oxidising conditions. Our findings therefore shine light on high-valent metal oxidants based on TAMLs and other potential non-innocent ligands and open new avenues for oxidation catalyst design.